2017
DOI: 10.4012/dmj.2016-229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resin infiltration on demineralized root surface: An <i>in vitro</i> study

Abstract: The aim of this study was to evaluate the effect of resin infiltration on root caries induced by Streptococcus mutans biofilms. Human premolar specimens were divided to 5 groups: negative control (NC), Clearfil SE Bond (SEB), Icon-etch120s+Icon-infiltrant (HA120), Icon-etch10s+Icon-infiltrant (HA10) and K-etchant10s+Icon-infiltrant (PA10). The resin penetration was observed by fluorescent microscope. Biofilm-induced demineralization was conducted again and observed by swept-source optical coherence tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…The system integrates a high-speed frequency and swept external-cavity laser. The wavelength ranges from 1,260 to 1,360 nm centered at 1,310 nm at 20 kHz sweep rate 15) . A custom code in the image analysis software (Image J, version 1.48; National Institutes of Health, Bethesda, MD, USA) was used to read the raw data of SS-OCT.…”
Section: Specimens Preparationmentioning
confidence: 99%
“…The system integrates a high-speed frequency and swept external-cavity laser. The wavelength ranges from 1,260 to 1,360 nm centered at 1,310 nm at 20 kHz sweep rate 15) . A custom code in the image analysis software (Image J, version 1.48; National Institutes of Health, Bethesda, MD, USA) was used to read the raw data of SS-OCT.…”
Section: Specimens Preparationmentioning
confidence: 99%
“…Zhou et al, in their study, evaluated the effect of infiltration on root caries induced by Streptococcus mutans biofilm. The researchers demonstrated that the microhardness of the tooth surface and resistance to caries increased significantly after the application of Icon infiltrant [ 51 ]. Yazkan and Gurdogan et al in their study confirmed that the application of Icon infiltrant increased the microhardness of the enamel surface [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al also noted that Icon resin causes an increase in surface roughness compared to a decalcified surface without application of the infiltrant. That research may suggest that Icon resin application tends to increase plaque accumulation on the tooth surface at the application site [ 51 ]. M-Skucha Nowak et al in their previous study pointed out that the commercial preparation Icon does not meet one of the main characteristics of a dental infiltrant, namely, it does not have a component responsible for bacteriostaticity [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of demineralized enamel prior to establishing enamel bond improved bond strength and durability 17,18 . However, in order to improve penetration of the infiltrant, surface pretreatments as application of hydrochloric or phosphoric acids are used causing substantial further loss of an already weakened enamel 19,20 .…”
Section: Remineralization Of Early Carious Enamel (Ece)mentioning
confidence: 99%